Saccadic eye movements associated with executive function decline in mild cognitive impairment and Alzheimer's disease: Biomarkers (non‐neuroimaging) / novel biomarkers. (7th December 2020) - Pereira, Marta Luisa Goncalves de Freitas; Villa, Martina; Koh, Do Hyong; Camargo, Marina von Zuben de Arruda; Belan, Ariella Fornachari; Radanovic, Marcia; Pomplun, Marc; Forlenza, Orestes Vicente
Abstract: Background: Abnormalities in eye movement metrics have been related to cognitive decline in dementia (Garbutt et al., 2008; Crawford et al., 2005), however, little is known about its association with executive dysfunction prior to the onset of Alzheimer's disease (AD). The objective of this study was to determine whether older adults with mild cognitive impairment (MCI) or incipient dementia due to AD display subtle signs of impairment in executive functioning as compared to healthy controls, through the analysis of eye movement behavior. Method: 93 elderly individuals were allocated into three groups according to cognitive status: normal controls (CTRL, n=28), mild cognitive impairment (n=44) and Alzheimer's disease (n=21). All groups were tested with an eye tracking‐assisted protocol composed of a prosaccade (PS) and an anti‐saccade (AS) task. The PS task required a fast, automatic saccade towards a peripheral target stimulus. In the AS task (measure of executive functioning), subjects had to inhibit an prosaccade towards the target stimulus and initiate a voluntary saccade in the opposite direction. Result: The PS task revealed a similar saccadic performance across the three groups. The AS task had a greater impact on the frequency and latency of eye movement metrics in each group, with AD subjects showing a greater executive decline than CTRL and with MCI group performing intermediately. MCI were similarly impaired as AD in their voluntary saccadic reaction times, with a longer time to correct erroneous saccades. Correlations revealed relationships between eye movement metrics in the AS and measures of inhibitory control, attention, working memory and self‐monitoring. Conclusion: The three groups showed a similar pattern of eye movements in the PS task, with both patients groups revealing a preserved automatic saccadic control compatible with the pattern observed in healthy ageing. AS task confirmed that cognitive impairment in the MCI‐AD continuum affects eye movement patterns reflecting executive deficits in inhibitory control, working memory and executive‐attention control subjacent to voluntary saccades. MCI revealed an intermediary impairment in these executive domains, as compared to AD (highest impairment) and CTRL. However, they showed significant increased response times similar to AD subjects, in order to overcome these deficits.